JOGOKARIYAN MOSQUE ZAKAT MANAGEMENT MODEL - Furqonul Haq (AL-ITTIFAQ Jurnal Ekonomi Syariah, 2025)
Jogokariyan Mosque is one of the most famous mosques in Indonesia. This mosque is renowned for its achievements and contributions to Muslims in Indonesia, especially Muslims in Yogyakarta. These achievements and contributions are certainly influenced by the good mosque management carried out by the Jogokariyan Mosque administrators, one of which is related to zakat management. This research aims to determine zakat management at Jogokariyan Mosque. The results found that in general, the Jogokariyan Mosque zakat management model consists of four stages: mapping, service, empowerment, and guidance. It can also be concluded that the zakat database; baitul maal and the zero-balance principle; service transformation and community empowerment; and synergy of mosque faith in financial management are the main components in Jogokariyan Mosque zakat management. This research contributes to adding guidance or role models for other mosques in Indonesia in zakat management. Keywords: Mosque, Jogokariyan, Zakat